Application of Data Quality Assessment Methods to an LCA of Electricity Generation. - May, John R.
Background, Goal and Scope. For the life cycle assessment (LCA) tool to provide maximum benefit for the decision makers, the uncertainty of it results should be reported. Several methods for assessing uncertainty have been developed, but despite recent efforts, there remains disagreement about their merits. Objectives. The objectives of the study were to review several assessment methods for estimating numerical and qualitative uncertainty of impact scores and recommend an appropriate uncertainty assessment scheme. The methods review has been conducted on the basis of an LCA case study regarding the comparison of the use of either brown or black coals in Australian electricity generation. Results and Discussion. Each assessment method indicated greater uncertainty in the impact scores calculated for black coal use than for brown coal use. Due to overlap of the uncertainty ranges in calculated impact scores neither of the coals could be regarded environmentally preferred. Conclusion. Both qualitative and quantitative methods were found to provide useful information about the uncertainty of calculated impact scores for the case study. Methods that combine qualitative and quantitative uncertainty provided no additional benefits, and obscured much of the information gained from using qualitative methods. Recommendation and Outlook. It is recommended that LCA results should include separate numerical (using Monte-Carlo simulation) and qualitative uncertainty assessments. When the ranges of calculated impact scores for compared options overlap, the normalised difference method is recommended.
Keywords: Australian electricity generation; Coal; Data quality; Data uncertainty; Life cycle assessment (LCA).